Enhanced piezoelectric properties and electrocaloric effect in novel lead‐free (Bi0.5K0.5)TiO3‐La(Mg0.5Ti0.5)O3 ceramics. Issue 12 (11th June 2018) - Li, Feng; Lu, Biao; Zhai, Jiwei; Shen, Bo; Zeng, Huarong; Lu, Shengguo; Viola, Giuseppe; Yan, Haixue
Abstract: The crystal structure, electromechanical properties, and electrocaloric effect (ECE) in novel lead‐free (Bi0.5 K0.5 )TiO3 ‐La(Mg0.5 Ti0.5 )O3 ceramics were investigated. A morphotropic phase boundary (MPB) between the tetragonal and pseudocubic phase was found at x = 0.01‐0.02. In addition, the relaxor properties were enhanced with increasing the La(Mg0.5 Ti0.5 )O3 content. In situ high‐temperature X‐ray diffraction patterns and Raman spectra were characterized to elucidate the phase transition behavior. The enhanced ECE (Δ T = 1.19 K) and piezoelectric coefficient ( d 33 = 103 pC/N) were obtained for x = 0.01 at room temperature. Meanwhile, the temperature stability of the ECE was considered to be related to the high depolarization temperature and relaxor characteristics of the Bi0.5 K0.5 TiO3 ‐based ceramics. The above results suggest that the piezoelectric and ECE properties can be simultaneously enhanced by establishing an MPB. These results also demonstrate the great potential of the studied systems for solid‐state cooling applications and piezoelectric‐based devices.